If you were here - Stinson, Kathy (Greystone Kids ; David Suzuki Institute, 2025)
"In this beautiful ode to nature and mindfulness, a child sets out to explore the environment around their home, using all their senses. Yet, someone important is missing, someone the child wishes could be there on the journey. Expressive text by Kathy Stinson leaves room for readers' own interpretations about who the child in the story might be missing, while Indigenous illustrator Maya McKibbin's gorgeous images capture the lush beauty of the natural world and the tenderness of a child's emotions."--